2005
DOI: 10.1016/j.ejcts.2004.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ascending aorta replacement on aortic root dilatation

Abstract: Both the increase of aortic root diameter and the progressive worsening of aortic valve insufficiency seem to justify a more aggressive treatment of the aortic root at the time of surgery for acute aortic dissecting aneurysm but not for chronic atherosclerotic non-dissecting aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Sparing the root is the technically more simple approach compared with root replacement procedures (composite replacements, valvesparing, remodeling, and so forth) because of lack of coronary artery reimplantation, and results in excellent clinical outcomes [9,[19][20][21][22]. Leaving the root behind in ascending aortic replacements, both De Paulis and colleagues [23] and Park and associates [24] noted that neither a progressive dilation of nonreplaced sinuses nor an incidence of root reoperations is evident in aneurysm patients, in contrast to aortic dissection. Their findings support the thrust of the current paper.…”
Section: Discussionmentioning
confidence: 99%
“…Sparing the root is the technically more simple approach compared with root replacement procedures (composite replacements, valvesparing, remodeling, and so forth) because of lack of coronary artery reimplantation, and results in excellent clinical outcomes [9,[19][20][21][22]. Leaving the root behind in ascending aortic replacements, both De Paulis and colleagues [23] and Park and associates [24] noted that neither a progressive dilation of nonreplaced sinuses nor an incidence of root reoperations is evident in aneurysm patients, in contrast to aortic dissection. Their findings support the thrust of the current paper.…”
Section: Discussionmentioning
confidence: 99%
“…De Paulis et al have reported that patients with nondissecting ascending aortic aneurysms can safely undergo supra‐coronary aortic replacement by noncompliant Dacron graft without increasing the risk of developing pathology of the aortic root. On the other hand, patients with acute dissecting aneurysm involving the aortic root have high incidences of aortic root dilatation, redissection or both which in some cases will dictate a second corrective operation 10 …”
Section: Discussionmentioning
confidence: 99%
“…C. A more pronounced root involvement reasonably and intuitively may support a pronounced progression of the aortic pathology. The dissection of all aortic sinuses [35] or its extension into the coronary ostia [2], seem to predict a high risk for reoperation; the aneurysmal evolution is more pronounced in a dissected aorta than in case of atherosclerotic aneurysm [36]. Similarly, patients with preoperative cardiac malperfusion, seen as a marker of severity of dissection of the coronary sinus(es), experience a higher rate of proximal aorta redo procedures during the follow up [37].…”
Section: Risk Factors Of Proximal Reoperation After Supracoronary Aormentioning
confidence: 95%